Development of a tissue engineered, in vitro model of smooth muscle contraction - Bridge, Jack Christopher (2016)
Smooth muscle (SM) tissue is found in many parts of the body, primarily in sheets or bundles surrounding hollow organs. The main function of the tissue is the regulation of organ tone via its contractile state. Dysfunction of SM in diseases such as asthma and atherosclerosis affect millions worldwide. Current methods for studying SM primarily rely on ex vivo animal tissues or 2D in vitro models. Animal models do not accurately recreate human disease states and 2D models are cultured on stiff surfaces lacking the elastic properties and 3D morphology found in natural extracellular matrix in vivo. Therefore it is desirable to develop both an in vitro model of SM that possesses the ability to contract and a method in which this contraction can be measured. In order to achieve this, primary rat aortic SM cells and primary human airway SM cells were cultured in collagen hydrogels; both free floating in the form of collagen disks and under uniaxial tension in order to generate aligned SM collagen constructs. When stimulated with contractile agonists, these constructs contract in a uniaxial fashion. The design of the constructs allows them to be attached to a force transducer allowing the physical force of contraction to be measured. The force of contraction was dependant on the agonist concentration and could be antagonised by the presence of an L-type calcium channel blocker. In order to improve the alignment and uniformity of the smooth muscle population a range of aligned electrospun scaffolds were produced from polyethylene terephthalate (PET), cross-linked gelatin and cross-linked gelatin methacrylate (GelMa). The average fibre diameter of the scaffolds ranged from approximately 200 nm to several micrometres. Additionally the Young’s moduli of the scaffolds ranged from around 1x105 to 1x108 Pa. In all cases, scaffolds were highly aligned; alignment was achieved by using a rapidly rotating collector mandrel. Culture of primary SM cells upon these scaffolds showed that the cells readily adhered to and proliferated upon the scaffolds over a 10 day culture period. The cells formed a highly aligned population following the topographical cues of the aligned fibrous scaffolds. Additionally, the cells stained positive for SM markers in all cases, indicative of a contractile phenotype. When stimulated with 100 µM UTP, the SM cells were able to contract the gelatin and GelMa scaffolds but not the PET scaffolds. SM seeded GelMa scaffolds were cultured for 10 days prior to attachment to the previously mentioned force transducer apparatus. Upon stimulation the seeded scaffolds contracted generating forces greater than those achieved by the hydrogel model, and was reproducible over several experiments.